PEMISAHAN KONJAK GLUKOMANAN MENGGUNAKAN MEMBRAN ULTRAFILTRASI - Yusiana Dewi Afriyani; Anisah Nirmala; Nita Aryanti (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
Glucomannan is a polysaccharide from hemicelulose variety that consist of the chain bunch of galactose, glucose and mannose. Glucomannan can be produced from porang (Amorphallus konjac) with isolation method using enzyme amylase where carbohydrate structure from the material will be broken to be monomers glucose such as galactose, glucose and mannose. One of the efford for increasing yhe quality and pureness of glucomannan can be used separation method using ultrafiltration membrane. To know the potential of ultrafiltration membrane for purification glucomannan will be done research for separation of glucomannan solution using ultrafiltration membrane. The membrane used in this experiment is Poly ether sulfon with pores 20 kda. This research used feed concentration of 0.5 gr/L and 1.5 gr/L, with operation pressure 1 bar, 2 bar and 3 bar. The characteristic of KGM showed that the KGM having particle size of 81.2 to 186 μm. The membrane permeability is 11.87 L/m2 h bar with porous assimetric type. Flux profile show that the increase of pressure will decrease the membrane flux. In addition, the membrane rejection is higher for pressure 3 bar than 1 bar and 2 bar. However at pressure of 2 and 3 bar membrane rejection decrease with the increase of concentration due to lower permeate mass transfer. Moreover, low permeate flux is caused by fouling and polarization of concentration. We suggest for the next research about fouling affect and polarization of membrane ultrafiltration.